Optimizing Precision of Hypertension Care to Maximize Blood Pressure Control: A Pilot Study Utilizing a Smartphone App to Incorporate Plasma Renin Activity Testing - Mai Mehanna; Yiqing E. Chen; Yan Gong; Eileen Handberg; Brittney Roth; Jessica De Leon; Steven M. Smith; Jonathan G. Harrell; Rhonda M. Cooper‐DeHoff (Wiley, 2021)
Only half of patients with hypertension (HTN) respond to any given antihypertensive medication. Heterogeneity in pathophysiologic pathways underlying HTN is a major contributor. Personalizing antihypertensive therapy could improve blood pressure (BP) reduction. The objective of this study was to assess the effect of pragmatic implementation of a personalized plasma renin activity (PRA)‐based smartphone app on improving BP reduction. Patients with untreated or treated but uncontrolled HTN were recruited. BP and PRA were measured at baseline with final BP measured at 6 months. Patient's information was entered into the app and treatment recommendations were returned. Clinicians were at liberty to follow or disregard the app's recommendations. BP levels and percent BP control among patients whose clinicians did and did not follow the app's recommendations were compared using independent t‐test and Fisher's exact test, respectively. Twenty‐nine European American patients were included (38% women) with mean age of 52 ± 9 years and median PRA of 1.3 ng/mL/hr (interquartile range 0.5-3.1 ng/mL/hr). Participants whose clinicians followed the app's recommendations (n = 16, 55%) as compared with those whose clinicians did not (n = 13, 45%), had a greater reduction in 6‐month systolic BP (−15 ± 21 vs. −3 ± 21 mm Hg; adjusted‐P = 0.1) and diastolic BP (−8 ± 8 vs. −1 ± 8 mm Hg; adjusted‐P = 0.04). BP control at 6 months tended to be greater among patients whose clinicians accepted the app's recommendations vs. those whose clinicians did not (63% vs. 23%, P = 0.06). This pilot study demonstrates that acceptance of the app's recommendations was associated with a greater BP reduction. Future studies to confirm these pilot findings are warranted.